Direct and indirect relations between parent–child attachments, peer acceptance, and self-esteem for preschool children - Pinto, Alexandra Maria Pereira Inácio Sequeira (2015)
The present study aims to test Bowlby's suggestions concerning relations between the child's attachment quality with parents and subsequently constructed models of self-worth during early childhood. In most research on this question, attachment with mothers is considered in relation to self-worth but the child's attachment with fathers is not. Neither has the peer group been studied as an influence on child self-esteem, in the context of attachment research. This study addresses these relatively unstudied influences on child self-esteem. Attachment security to mother and father was measured by the Attachment Behavior Q-Set at two and half years of age. At five years of age social acceptance was measured using two sociometric techniques, and the self-esteem with the California Child Q-Sort. Our analyses indicated that security of the attachment to father and peer acceptance are both unique, significant predictors of the childrens' self-esteem. The security of the attachment to mother was also related to child self-esteem but did not emerge as a uniquely significant predictor. Peer acceptance appeared to moderate of the effect of the security of the attachment to father on the self-esteem of children. Our results extend the relatively sparse literature relating early attachments to self-esteem during early childhood.